How do laparoscopic versus open surgical repair techniques compare in terms of patient recovery, complication rates, and mortality for perforated peptic ulcers : A Systematic Review - Ruditya Lukman Hakim; Rezky Putri Wahyu Agustine (International Medical Journal Corp. Ltd, 2025)
Introduction: Perforated peptic ulcer (PPU) is a life-threatening surgical emergency traditionally managed by open laparotomy. In recent decades, laparoscopic repair has emerged as a prominent minimally invasive alternative. While benefits such as reduced pain and shorter hospital stays are reported, concerns remain regarding longer operative times, specific complications like suture leakage, and inconclusive mortality data. This systematic review aims to comprehensively compare patient recovery, complication rates, and mortality between laparoscopic and open surgical techniques for PPU. Methods: A systematic review was conducted following the PRISMA 2020 guidelines. A comprehensive search of five electronic databases (PubMed, Springer, Semantic Scholar, Google Scholar, Wiley Online Library) was performed to identify comparative studies published in the last decade. The review included randomized controlled trials and observational studies comparing laparoscopic and open repair in adult patients with PPU. After screening and eligibility assessment, 26 studies were included for qualitative synthesis. Results: The synthesis of 26 studies revealed that laparoscopic repair was consistently associated with a significantly shorter postoperative hospital stay (reported in all 16 studies measuring this outcome) and reduced postoperative pain. Furthermore, rates of overall complications and surgical site infections were substantially lower in the laparoscopic group. Conversely, laparoscopy was associated with a longer mean operative time in a majority of studies and a potentially increased risk of suture leakage. The evidence regarding mortality remained inconclusive, as most individual studies were underpowered to demonstrate a statistically significant difference. Conclusion: Laparoscopic repair offers clear and significant advantages over open surgery regarding postoperative recovery, including shorter hospitalization, less pain, and markedly fewer surgical site infections. It should be considered the standard of care for clinically suitable patients. However, the decision must be tempered by the realities of longer operative times and a small but serious risk of suture leakage, which necessitates careful patient selection and adequate surgical expertise. Future large-scale trials are needed to provide definitive conclusions on mortality.